Survival rate and prognostic factors of death among patients with non-hodgkin lymphoma in Kelantan from 2008-2017 - Nazmi, Omar (2024)
Background: Non-Hodgkin lymphoma is the 12th most common cancer globally, the 4th in Malaysia, and the 5th in Kelantan. Studying the survival rate, median survival time, and prognostic factors of non-Hodgkin Lymphoma can provide valuable insights specific to the Kelantan population and assist in developing better intervention programs. Improving the survival rate aligns with Sustainable Development Goal 3.0, which aims to ensure healthy lives and promote well-being. Objectives: This study aimed to describe Kelantan's non-Hodgkin lymphoma survival rate and median survival time. This study also aimed to determine the prognostic factors for death among non-Hodgkin lymphoma patients in Kelantan. Methodology: A retrospective record review was conducted using secondary data among the patients diagnosed with non-Hodgkin lymphoma from January 1st, 2008, until December 31st, 2017. An additional five-year follow-up until December 31, 2022, was done to verify the patient's status. The inclusion criteria included Malaysian patients aged 15 years or older with Hodgkin lymphoma who resided and registered in the Kelantan Cancer Registry between January 1st, 2008, and December 31st, 2017. The exclusion criteria included missing data greater than 30% and duplicate data. All patients who fulfilled the inclusion and exclusion criteria were included in the study. The data were analysed using SPSS version 28. Kaplan-Meier was used to calculate survival estimates, while the Cox proportional hazards model was used to determine prognostic factors. Results: There were 448 patients included in this analysis. The mean (SD) age at diagnosis was 50.19 (18.01). Most patients were male, 60.7% and Malay 96.4%. The most common histological subtypes were Mature B-cell neoplasm (74.3%) and the aggressive type (87.3%). The 5-year overall survival rate was 28.3% (95% CI: 24.1, 32.5). The median survival time of ≥ 15-year-old non-Hodgkin lymphoma patients in Kelantan was 9.01 (95% CI: 5.95, 12.06) months, respectively. The proportional Hazard Cox model showed that age more than 60 years old had a higher hazard of death of 1.55 (Adj. HR:1.55; 95% CI: 1.24, 1.93; p=<0.001) times compared to age less 60 years old; being male had a higher hazard ratio of death of 1.39 (Adj. HR: 1.39; 95% CI: 1.12, 1.73; p =0.003) times compared to female; and being in stage IV had a higher hazard ratio of death of 1.88 (Adj. HR: 1.88; 95% CI: 1.17, 3.04; p=0.010) times compared to stages I and II. When other variables were adjusted, the patient who did not undergo chemotherapy treatment had a significantly higher hazard of death of 1.50 (Adj. HR: 1.50; 95% CI: 1.18, 1.92; p = 0.001) times compared to the patient who received chemotherapy. Conclusion: The overall 5-year survival rate was 28.3% (95% CI: 24.1, 32.5). The median survival time of ≥ 15-year-old non-Hodgkin lymphoma patients in Kelantan was 9.01 (95% CI: 5.95, 12.06) months. The significant factors of death among non-Hodgkin lymphoma patients in Kelantan were age ≥ 60, male gender, stage IV, and patients who did not receive chemotherapy treatment, which was consistent with other studies globally. This study provides essential data for policymakers to design targeted health interventions, such as early detection and treatment programs, to increase survival rates, reduce non-Hodgkin lymphoma mortality, and improve Kelantan's blood cancer care services.